Mitigation of Railway Traffic Induced Vibrations: The Influence of Barriers in Elastic Half-Space. (14th June 2009) - Buonsanti, Michele; Cirianni, Francis; Leonardi, Giovanni; Santini, Adolfo; Scopelliti, Francesco
Abstract : In this paper, the problem of vibrations induced by trains and their propagation through the soil is studied. Particular attention is focused on the vibration induced by trains in motion and on the effects of such vibrations on the foundations of buildings in proximity of the tracks. The interaction between propagating waves induced by trains in motion and buildings foundations is a problem which does not admit a straightforward analytical solution; thus a solution is given by the use of a model based on the finite elements method. Firstly, we analyze the theoretical aspects of the problem by considering constant or harmonic loads moving along a straight railway track; then, we define a transfer function soil-railway and the response function of the entire system. The study aims to address the wave propagation in an elastic semi-space and the presence in the ground of a discontinuity element, such as a barrier of a given depth is considered. The efficiency variation of barriers is analyzed in function of the different materials used, and different numerical simulations are analyzed in order to study how the wave propagation and the track-soil interaction are influenced by the membrane, seen as damping barrier.